Effects of different dietary protein sources on the immunological and physiological responses of marron, Cherax cainii (Austin and Ryan, 2002) and its susceptibility to high temperature exposure. Issue 88 (May 2019) - Saputra, Ishaaq; Fotedar, Ravi; Gupta, Sanjay K.; Siddik, Muhammad A.B.; Foysal, Md Javed
Abstract: A two phased feeding trial was conducted to evaluate the effects of alternative protein sources on the immunophysiological responses of marron. During the phase I, marron were fed with five alternative protein supplemented diets for 90 days, while in phase II, the same marron were exposed to elevated temperature (30 °C) and their immunophysiological responses were investigated post exposure. Five isoproteic (crude protein 30%) and isoenergetic diets were prepared by containing fishmeal, poultry by-product meal, feather meal, lupin meal, and meat and bone meal as the main protein source. A hundred and fifty juvenile marron ( Cherax cainii ) of the average weight 9.09 ± 0.21 g were randomly distributed into 15 tanks (three replicates per feeding treatments). In the Phase I, general immune response parameters, such as, total haemocyte count (THC), proportion of hyaline cells, neutral red retention time (NRRT), phagocytic rate (PR), heamolymph bacteraemia, and condition indices of marron were investigated. The highest (P < 0.05) THC among dietary protein sources was obtained in marron fed with PbM at the end of experiment. Marron fed with FeM protein sources resulted in the highest survival rate followed by PbM fed group. Longer microvilli length (3.83 ± 0.18 μm) was demonstrated in marron fed with PbM diet. Diets containing FM and PbM protein sources revealed significantly (P < 0.05) lower number of microvilli/group than diets containing FeM and LM. The results demonstrated that different dietary protein sources in the marron diets did not detect significant (P > 0.05) change of the condition indices throughout the experiment period, however highest Hiw and Hid was recorded in marron fed with PBM at day 45. The PR of marron fed dietary protein from PbM did not change significantly after temperature exposure. Increased NRRT, PR and haemolymph bacteraemia was observed with dietary feeding of FM at the end of the trial. However, results revealed that PbM could be an alternative protein source for culture of marron as reflected in terms of increased THC, longer microvillus length and improved susceptibility to high temperature exposure. Overall, result could serve as useful baseline data in developing cost effective potential diets for marron aquaculture. Highlights: Dietary protein sources significantly affect the immunophysiological responses of marron. Increased THC and longest microvilli length were observed with dietary feeding of PbM. Improved susceptibility to high temperature exposure in marron was observed with PbM. PbM could be an alternative protein source for development of marron aquaculture.